GENDER AND ACQUISITION OF ENTREPRENEURSIP EDUCATION SKILLS IN NIGERIAN UNIVERSITIES - Alade, Feyi; Sule, Mary A.; Francisca, Odigwe (Advances in Social Sciences Research Journal, 2015)
For over a decade, Nigeria has been faced with unprecedented soaring rate of unemployment, and majority of the affected graduates are confused, discouraged, and deeply troubled about the future. Entrepreneurship education was introduced into University curricula to help solve this problem. This study investigates gender and acquisition of entrepreneurship education skills by undergraduate students in Nigerian universities. This survey design, utilized a validated questionnaire called “Entrepreneurship Education Skills and Self employment intentions from nine hundred (900) undergraduate students in three universities: Calabar, Port-Harcourt, and Benin. Multi-stage sampling technique was used. One hypothesis was stated and tested in the study using Independent T-test at α = 0.05. The result indicated a significant difference between male and female undergraduate in their entrepreneurship education skills. The result also shows that the male students showed superiority over their female counterparts only in their propensity to take risk and in ICT skills. The female students were better than the male students in sense of initiative, self efficacy, creativity, communication skill, and knowledge of entrepreneurship. Based on the findings of the study, recommendations were made.